2012
DOI: 10.5751/es-04507-170107
|View full text |Cite
|
Sign up to set email alerts
|

Logging Concessions and Local Livelihoods in Cameroon: from Indifference to Alliance?

Abstract: Sustainable forest management gives the opportunity to better integrate the way local populations use their customary "village terroirs" in the logging activities. This requirement is explicitly stated in all forest laws of the Congo Basin countries but its implementation on the field remains under documented. In Cameroon, 30 forest management plans (FMP) for logging concessions have been reviewed to assess how they effectively include customary use rights. The integration of use rights into the FMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 21 publications
2
36
1
2
Order By: Relevance
“…The Southern Cameroon case study illustrates the evolution of local tropical humid forest management systems in the face of an emerging 'community forests' policy (Lescuyer et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The Southern Cameroon case study illustrates the evolution of local tropical humid forest management systems in the face of an emerging 'community forests' policy (Lescuyer et al 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The development of scientific forestry established professional foresters as the only knowledgeable and legitimate forest managers, thus discarding farmers and local people. This has entailed important biases for rural forests management, as noted in the papers by Lescuyer et al (2012) in Cameroon, and Rives et al (2012) in Niger.…”
Section: Competing Visions Of the Forestmentioning
confidence: 99%
“…Rural forestry schemes focus globally on encouraging local people to access conventional forest management rather than adapting to rural forest management logic. Lescuyer et al (2012) show that the integration of local use rights or local knowledge and practices into community forest management plans is primarily formal. Kouplevatskaya and Buttoud (2008) showed that in France, even if local forest policies target rural development and farmers' participation, forest management still focuses on classical forest services (provision of timber and energy, protection of "remarkable" plant or animal species) and not on the real farmers' needs and interests.…”
Section: Do Sustainable Development Policies Help?mentioning
confidence: 99%
See 1 more Smart Citation
“…Legal extraction from these concessions requires plans for reforestation, minimizing the socio-cultural effect on the local people and the biological effect on the environment (MINAG 2009). Although many studies have explored the social, economic, and ecological effects of timber concessions (Uhl et al 1991, Verissimo et al 1992, Watson 1996, Lescuyer et al 2012, most have focused on the effects on lumber species targeted for extraction, and relatively few on game and other wildlife species (Rist et al 2011). However, it has been repeatedly shown that timber operations cause widespread negative effects on wildlife populations, including population declines and local extinctions, as well as other effects such as infant malnutrition, abandonment, and mortality (Thiollay 1992, Marsden 1998, Meijaard et al 2006.…”
Section: Introductionmentioning
confidence: 99%